2018
DOI: 10.3233/jad-180726
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Mouse Brains Exposed to Blast-Induced Mild Traumatic Brain Injury Reveals Changes in Axonal Proteins and Phosphorylated Tau

Abstract: Alzheimer’s disease (AD), the most prevalent form of dementia, is characterized by two pathological hallmarks: Tau-containing neurofibrillary tangles and amyloid-β protein (Aβ)-containing neuritic plaques. The goal of this study is to understand mild traumatic brain injury (mTBI)-related brain proteomic changes and tau-related biochemical adaptations that may contribute to AD-like neurodegeneration. We found that both phosphorylated tau (p-tau) and the ratio of p-tau/tau were significantly increased in brains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 63 publications
(76 reference statements)
3
51
0
Order By: Relevance
“…However, by examining the nominally significant genetic locus associated with the metabolite on chromosome 10 (BP 60,794,328-61,050,339), nearby genes and phenotypes associated with those genes were identified (genes included PHYHIPL, TRAF6P1, LINC00844, and FAM13C; phenotypes included DNA methylation, sleep duration, and QT-interval duration in Trypanosoma cruzi seropositivity). Together, these findings support and potentially shed light on the biological mechanism for metabolite X-24295's association with PTSD, as PTSD has been shown to be related to traumatic brain injury 68 (which has been associated with PHYHIPL in mice 69 ), altered DNA methylation 70 , and sleep disturbances 71 . These genetic annotations may also aid in the identification of the metabolite itself, as has been demonstrated by other metabolome-wide GWAS analyses 17 .…”
Section: Discussionmentioning
confidence: 62%
“…However, by examining the nominally significant genetic locus associated with the metabolite on chromosome 10 (BP 60,794,328-61,050,339), nearby genes and phenotypes associated with those genes were identified (genes included PHYHIPL, TRAF6P1, LINC00844, and FAM13C; phenotypes included DNA methylation, sleep duration, and QT-interval duration in Trypanosoma cruzi seropositivity). Together, these findings support and potentially shed light on the biological mechanism for metabolite X-24295's association with PTSD, as PTSD has been shown to be related to traumatic brain injury 68 (which has been associated with PHYHIPL in mice 69 ), altered DNA methylation 70 , and sleep disturbances 71 . These genetic annotations may also aid in the identification of the metabolite itself, as has been demonstrated by other metabolome-wide GWAS analyses 17 .…”
Section: Discussionmentioning
confidence: 62%
“…According to the severity of the injury, mild, moderate, and severe TBI can be selected. In general, the elevated level of phosphorylated Tau, the expression of Aβ, degradation of white matter, BBB dysfunction as well as neurogenic inflammation in hippocampus were observed in TBI models …”
Section: Traumatic Brain Injuries‐induced Ad Animal Modelmentioning
confidence: 99%
“…TBI-induced AD models have been developed to mimic the sAD pathological changes in the brain. Controlled cortical impact (CCI) model,[102][103][104] fluid percussion injury (FPI) model,[105][106][107][108] weight drop model,103,[109][110][111] and blast injury (BI) model[112][113][114][115] can be used to induce TBI in animals. According to the severity of the injury, mild, moderate, and severe TBI can be selected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, progressive spreading of tau proteinopathy has been triggered in wild-type mice by impact or blast TBI [26][27][28][29]. Quantitation of tau and phosphorylated tau (p-tau) in mice show that tau and p-tau levels are significantly changed within 1 day after blast, then return to the pre-blast stage when mouse brains were examined at 15 weeks post-blast [30], consistent with previous findings in mini-pigs [31] and mice [32]. Other studies conducted in mice have shown long-term persistence and even progression of blast-and impact-induced p-tauopathy [26-28, 33, 34].…”
Section: Introductionmentioning
confidence: 99%